Modality in the moves of the discussion section of research articles - Ali Mansouri Nejad; Omer Hassan Ali Mahfoodh (Indonesian Journal of Applied Linguistics, 2023)
Various studies have been conducted on the rhetorical mechanism of Research Articles (RAs). However, the use of modal verbs in the Discussion section of a Research Article (RA) has not been adequately addressed. Thus, this study analysed modal verbs within the four generic moves in the Discussion sections of RAs using the model of Kanoksilapatham (2007). A corpus of 60 RAs written in English was selected from four Applied Linguistics journals: Language Testing, TESOL Quarterly, Pragmatics, and Second Language Research. The analysis of the corpus included two phases: (1) the identification of moves in the Discussion sections and (2) identification of modal verbs and their use within the identified generic moves in the Discussion sections. Chi-square was used to determine the distribution of modal verbs within the moves in the Discussion sections in each journal. The study revealed the significant distribution of modal verbs within three moves: 2, 3, and 4. The study also showed that the way modal verbs are distributed reflects the importance of their use as they have pragmatic functions in the Discussion section of a RA. It is hoped that this genre-based analysis of modal verbs in the Discussion section can make novice writers aware of how expert writers use modal verbs effectively in the moves of the Discussion section.